The study of length of umbilical cord and fetal outcome - Rawal, Naisargee G.; Yadava, Pushpa A.; Vyas, Rupa C.; Jani, Shashwat K.; Dangar, Kashmira V.; Patel, Heny J.; Asudani, Nitya P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The umbilical cord is vital for fetal development, and its length can influence intrapartum complications, mode of delivery, and perinatal outcomes such as FGR, oligohydramnios, preterm delivery, operative delivery for fetal distress, fetal demise/stillbirth, meconium-stained liquor, cord accidents. This study investigated the impact of umbilical cord length on these factors in singleton pregnancies. Methods: A retrospective study was conducted at SVP Hospital, Ahmedabad, from June 2024 to June 2025, involving 300 randomly selected singleton pregnancies. Inclusion criteria included primigravida and multigravida subjected to ultrasound, excluding malpresentations and multiple gestations. Data on cord length, nuchal loops, true knots, mode of delivery, and perinatal outcomes, including intrauterine fetal demise (IUFD), were analysed. Results: Of the 300 cases, 58% were booked, and 68% were multigravida. Cord lengths of 66-75 cm were most common (32.33%), with short cords (<45 cm) and long cords (>90 cm) comprising 5.32% and 8.66%, respectively. Short cords were associated with a 31.25% IUFD rate, compared to 11.5% for long cords and 2.7% for medium cords (46-90 cm). Nuchal cords increased caesarean delivery rates (53.33% for one loop, 85.70% for three loops). True knots had a lower caesarean rate (42.86%). The overall IUFD rate was 5%. Conclusions: Short and long umbilical cords are associated with increased IUFD and caesarean delivery rates, particularly with multiple nuchal loops. Antenatal ultrasound is crucial for identifying cord abnormalities to optimize outcomes.